Pengaruh Penggunaan Dompet Digital Terhadap Perilaku Konsumtif Masyarakat Kelurahan Cakung Timur, Kecamatan Cakung, Jakarta Timur: The Effect of Digital Wallet Use on Consumptive Behavior in Cakung Timur Village, Cakung District, East Jakarta - Herlizah, Novita; Subali, Subali (Efektor, 2023)
The development of financial technology has changed people’s lifestyles to become completely digital. Transactions in an all-digital world besides being able to use cash, can also use a digital wallet. This study aims to determine the effect of using a digital wallet on the consumptive behavior of the people of Cakung Timur Village, Cakung District, East Jakarta. This study used a quantitative approach with a study population of 61.891 people. The number of samples used was 120 samples with the purposive sampling technique. The data collection process was carried out by distributing questionnaires via Google form and a likert scale as a data measurement scale. Then the classic assumption test is performed, namely the normality test, regression linearity test, simple regression analysis, correlation coefficient test and coefficient of determination, t statistical test. The results showed that digital wallets had a positive and significant effect of 37,4% on the consumptive behavior of the people of Cakung Timur Village, Cakung District, East Jakarta.